Method for preparing composite pellets from edible seaweed

The preparation of porous carbon/silicate composite pellets through sea vegetables solves the problems of high pressure demand and insufficient material strength when storing methane, and achieves an efficient and environmentally friendly methane storage effect.

CN119158541APending Publication Date: 2024-12-20JIANGSU OCEAN UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292594.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has problems with high pressure demands and insufficient mechanical strength of materials in the storage of methane, and traditional methods have a great impact on the environment.

Method used

Using sea vegetables as the precursor, it is prepared by washing, drying, cutting into small sections and slowly heating and activation under the protection of inert gas, and mixed with clay to sinter it into rigid porous carbon/silicate composite pellets. in filling the adsorption natural gas storage tank.

Benefits of technology

Porous carbon materials with high specific surface area and thermal stability are achieved, which improves the mechanical strength and methane storage capacity of the material, and has a simple process and a small environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158541A_ABST
    Figure CN119158541A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing composite pellets by using edible seaweed, which comprises the following steps: washing and drying edible seaweed, cutting the edible seaweed into small sections, and uniformly dispersing the small sections in a reaction boat; the reaction boat is placed in a furnace, and inert gas purging is conducted on the furnace for 1-10 h under the condition that the flow speed of inert gas flow is 3-10 ml / min; under the protection of inert gas, the furnace temperature is slowly increased to the activation temperature of 650-1000 DEG C from the room temperature, the temperature rise speed of slow temperature rise is 2-5 DEG C / min, and after activation is conducted for 60-120 min, a porous silicon-carbon composite material is obtained; the obtained porous silicon carbon material is compositely cooled to the room temperature under the protection of inert gas, acid pickling impurity removal and water washing are carried out until the material is neutral, then drying is carried out, then heating is carried out for 60 minutes at the same temperature, and program control cooling is carried out to the room temperature. The process is simple, and no auxiliary agent is needed. The prepared porous silicon-carbon composite material has the advantages of higher specific surface area, high thermal stability, uniform pore size distribution and better methane gas storage property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a method for preparing composite pellets by using seaweed. Background Art

[0002] In today's world of highly developed civilization and rapid economic development, in order to cope with the growing demand for energy and the challenge of gradually depleting energy, we urgently need low-cost, environmentally friendly, abundant energy materials and related energy storage systems. Silicon is the eighth most abundant element in the universe and the second most abundant element in the earth's crust, accounting for 26.4% of the total mass of the earth's crust. It exists in the form of silicates and silicon dioxide in the earth's crust. Carbon is the 17th most abundant element. Due to its abundant reserves, chemical stability and thermal stability, it has been widely studied and applied. Due to its special porous structure, especially some activated carbon materials with large specific surface area (>1000m2g-1) and large pore volume (>0.5cm3g-1) and silicate materials represented by zeolite molecular sieves, there is potential research value in the fields of energy application such as catalysis and energy storage.

[0003] Methane, as a clean energy (the main component of natural gas), has been used in automobiles. Since the methane combustion process requires less air, its combustion performance is stronger than traditional gasoline. At the same time, the production of carbon dioxide and nitrogen oxides is greatly reduced, allowing the engine to operate at a higher efficiency. There are currently four main methods for storing methane: liquefied natural gas (LNG), compressed natural gas (CNG), adsorbed natural gas (ANG), and natural gas hydrate (NGH). Among them, the ANG method requires less pressure, has a large storage capacity, does not require the shape of the storage tank, and has lower requirements for thickness and compressive strength. Summary of the invention

[0004] The purpose of the present invention is to design a method for preparing composite pellets using seaweed. The method has a simple process, does not require auxiliary agents during the preparation process, has no or little impact on the environment, increases the bulk density of powder compared to powder, and increases the mechanical strength of the material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing composite pellets using seaweed, characterized in that: the method is as follows: Step 1: Wash, dry and cut the seaweed into small pieces, and evenly spread them in a reaction container; Step 2: Place the reaction vessel in a furnace and purge the furnace with inert gas at a flow rate of 3-10 ml / min for 1-10 h; Step 3: Under the protection of inert gas, slowly increase the furnace temperature from room temperature to the activation temperature of 650-1000°C at a rate of 2-5°C / min. After activating for 60-120 minutes, a porous silicon-carbon material is obtained; Step 4: Cool the porous silicon-carbon material obtained in step 3 to room temperature. The cooling process is carried out under the protection of inert gas. After acid washing to remove impurities and water washing to neutrality, it is dried, heated at the same temperature for 60 minutes, and cooled to room temperature. Step 5: The porous carbon obtained in step 4 is mixed with clay, pressed into pellets, and sintered at 600-1000°C to obtain rigid porous carbon / silicate composite pellets suitable for filling into ANG tanks.

[0006] Furthermore, the reaction container is made of quartz, nickel, ceramic or corundum.

[0007] Furthermore, the inert gas is nitrogen or argon, the inert gas flow rate is 3 ml / min, and the purge time is 2 h.

[0008] Furthermore, the furnace is a tubular furnace.

[0009] Furthermore, after ball milling in step 4, the product is washed with 10%-36.5% hydrochloric acid to remove impurities and washed with water until neutral and then dried.

[0010] Furthermore, the clay is high-silica clay, which is specifically one or more combinations of montmorillonite, bentonite, and kaolin. The granulation pressure is 10-40 MPa, and the sintering temperature is 650-1000°C.

[0011] The following beneficial effects can be obtained through the above technical solution: The method for preparing porous carbon materials of the present invention uses seaweed as a precursor, performs a programmed temperature increase under the protection of an inert gas flow, and maintains the temperature at an appropriate temperature, and utilizes the potassium salt and calcium salt contained in the precursor itself to self-activate the material, so as to pyrolyze the material to obtain porous carbon in the target composite material. The method for preparing porous carbon materials of the present invention is not only simple in process, but also does not require the use of an added activator; the method for preparing porous carbon materials of the present invention, the porous carbon / silicate composite pellets obtained have a high specific surface area and thermal stability, a uniform pore size distribution, and good capacitance properties and gas adsorption performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The thermogravimetric curve of the biomass carbon source obtained by heating at a rate of 5 degrees Celsius per minute in an air atmosphere; Figure 2 A is the infrared spectrum of the precursor in Example 1; B is the infrared spectrum of the porous carbon / silicate composite pellets in Example 1; Figure 3is a low-pressure nitrogen gas adsorption-desorption isotherm diagram of the porous carbon / silicate composite pellets in Example 1; Figure 4 is the pore size distribution diagram of the porous material in Example 1 according to the DFT method; Figure 5 is the X-ray diffraction spectrum of the porous carbon material in Example 1; Figure 6 is the high-pressure methane gas storage curve of the porous carbon / silicate composite pellets in Example 1; Figure 7 TGA thermogravimetric analysis curve of the sample; Figure 8 EDX test results of the sample Fig. 9 The SEM results of porous carbon. DETAILED DESCRIPTION

[0013] The following is combined with Figure 1-9 The present invention is further described as follows: A method for preparing composite pellets using seaweed, characterized in that: the method is as follows: Step 1: Wash, dry and cut the seaweed into small pieces, and evenly spread them in a reaction container; Step 2: Place the reaction vessel in a furnace and purge the furnace with inert gas at a flow rate of 3-10 ml / min for 1-10 h; Step 3: Under the protection of inert gas, slowly increase the furnace temperature from room temperature to the activation temperature of 650-1000°C at a rate of 2-5°C / min. After activating for 60-120 minutes, a porous silicon-carbon material is obtained; Step 4: Cool the porous silicon-carbon material obtained in step 3 to room temperature. The cooling process is carried out under the protection of inert gas. After acid washing to remove impurities and water washing to neutrality, it is dried, heated at the same temperature for 60 minutes, and cooled to room temperature. Step 5: The porous carbon obtained in step 4 is mixed with clay, pressed into pellets, and sintered at 600-1000°C to obtain rigid porous carbon / silicate composite pellets suitable for filling into ANG tanks.

[0014] The reaction container is made of quartz, nickel, ceramic or corundum.

[0015] The inert gas is nitrogen or argon, the inert gas flow rate is 3 ml / min, and the purge time is 2 h.

[0016] The furnace is a tubular furnace.

[0017] After ball milling in step 4, the product is washed with 10%-36.5% hydrochloric acid to remove impurities and washed with water until neutral and then dried.

[0018] The clay is high-silica clay, which is specifically montmorillonite, bentonite, kaolin or one or more combinations thereof. The granulation pressure is 10-40 MPa, and the sintering temperature is 650-1000°C.

[0019] This embodiment provides a method for preparing composite pellets using seaweed, comprising the following steps: (1) Wash, dry and cut the seaweed into small pieces, and evenly disperse them in a reaction boat; (2) placing the reaction boat in a furnace, and purging the furnace with inert gas at an inert gas flow rate of 3-10 ml / min for 1-10 h; (3) Under the protection of inert gas, slowly increase the furnace temperature from room temperature to the activation temperature of 650-1000°C, and the slow heating rate is 2-5°C / min. After 60-120 minutes of activation, a porous carbon material is obtained; (4) cooling the porous silicon-carbon material obtained in step (3) to room temperature, wherein the cooling process is carried out under the protection of an inert gas, and then drying after acid washing to remove impurities and water washing to neutrality, and then heating at the same temperature for 60 minutes, and cooling to room temperature under program control; (5) The porous carbon obtained in step (4) is mixed with a certain proportion of clay (montmorillonite, bentonite, etc.), pressed into pellets, and sintered at 600-1000 °C to obtain rigid porous carbon / silicate composite pellets suitable for filling into ANG storage tanks.

[0020] The BET specific surface area of ​​the porous carbon material prepared by the method under optimized conditions is 800-1500 square meters / gram, and the high-pressure methane storage performance of the porous carbon / silicate composite pellets is 400-500V / V by volume.

[0021] The seaweed used as the precursor of the porous silicon-carbon material contains lignin, a small amount of cellulose, hemicellulose, soluble polysaccharides and proteins, and there is a certain amount of potassium and calcium inside the plant. It is preferably from the Sargassum family of the Phaeophyta, and more preferably from the genus Sargassum.

[0022] In the process of preparing porous carbon / silicate composite pellets according to the present invention, the temperature control of the carbonization process in step (3) will affect the carbonization degree and carbonization quality of the porous carbon material. If the carbonization temperature of the precursor material is represented by T, the temperature of the carbonization process is preferably controlled at T±50°C. If the temperature is too low, carbonization cannot proceed. Although a certain degree of high temperature is conducive to improving the degree of carbonization and increasing the porosity, if the temperature is too high, the generated pores will be destroyed, affecting the uniform distribution of the material pores, and may also cause the collapse of the material skeleton. The present invention does not have strict restrictions on the heating equipment of the pyrolysis process, such as the heating furnace commonly used in the prior art, etc., and a tubular furnace is preferred because the temperature control of the tubular furnace can be completed by the thermocouple configured by itself, which is more convenient. The sintering process can preferably be carried out in a muffle furnace. The sintering process does not require high atmosphere. The muffle furnace can operate stably within the temperature range required for preparation, and has a larger space, which is convenient for mass preparation. Since the carbonization degree of porous carbon materials is related to their application fields, for example, pure carbonized materials can be used to manufacture electrode materials, and partially carbonized materials are expected to have potential applications in application fields with specific pore sizes and specific surface area requirements through further property tests. Therefore, the method of the present invention can conveniently control the carbonization degree of porous carbon-silicon composite materials by controlling the temperature of the carbonization process to a certain extent, so as to obtain porous materials for different purposes. When the temperature is raised in the program in step (3), the heating rate should not be too fast, because too fast a heating rate can easily lead to uneven heating, which in turn leads to uneven carbonization. The preferred heating rate is 2-5 degrees Celsius / minute, which can save time while ensuring uniform heating.

[0023] In the process of preparing the porous silicon-carbon composite material of the present invention, the carbonization degree can also be adjusted by the carbonization time. Generally, the longer the pyrolysis time, the more complete the carbonization. The preferred pyrolysis time is 60-120 minutes. If the time is too short, the carbonization degree of the product is low. If the time is too long, there will be no significant improvement in the properties, but it will increase the time and raw material costs.

[0024] Due to the characteristics of its structure and composition, seaweed has KCl and CaCl2 evenly distributed in the material. The porous carbon material prepared as a precursor can activate itself to form pores during the heating process, and can utilize all types of wood cellulose in seaweed (mainly lignin, a small amount of cellulose, and hemicellulose), and the solid content can reach more than 30%.

[0025] According to the principle of using materials from local sources, plants grow in completely different regions. As a warm temperate-subtropical plant, it is mainly distributed in the northwest Pacific Ocean. It is widely distributed in my country, especially in the southern coastal areas. In recent years, it has been cultivated on a large scale along the Zhejiang coast. It is distributed in Liaodong Peninsula, Shandong, and Leizhou Peninsula. In addition, it is also distributed in the southern part of Hokkaido, Honshu, Kyushu and the coast of North Korea. From the results of the N2 adsorption-desorption curve test, the carbon material prepared from Sargassum fusiformis is a microporous material with a narrow pore distribution range concentrated around 1nm ( Figure 4 , Figure 5 ) Materials with narrow pore size distribution have greater potential in application, and seaweed as a precursor does not require special methods to control the pore size, and has more practical application value. Microporous materials are usually ideal gas storage materials, and the methane storage capacity of porous carbon materials prepared from seaweed is at a relatively high level among carbon materials ( Figure 6 ), is an ideal gas storage material.

[0026] The seaweed raw materials used in the laboratory stage are untreated original materials. In actual industrial production, they can be extended to the seaweed residues that have been extracted with iodine or mannitol as carbon sources and silicon sources to prepare porous carbon-silicon composite materials, solving the problem of waste residue utilization while greatly reducing production costs. Example 1

[0027] This embodiment provides a porous carbon / silicate composite pellet and its preparation, and the technical scheme is as follows: (1) The carbonized precursor seaweed is fully dried and processed into small pieces so that the precursor can be better and more evenly dispersed in the container. The precursor material Sargassum fusiformis is preferably from the family Sargassum of the brown algae phylum, more preferably from the genus Sargassum, and contains a certain amount of potassium and calcium. The biomass material seaweed contains lignin, a small amount of cellulose, hemicellulose, soluble polysaccharides and proteins. (2) heating the seaweed from room temperature to 900° C. at a heating rate of 2° C. / min under the protection of an inert gas; the heating equipment may be a heating furnace commonly used in the prior art, preferably a tubular furnace; The carbonization temperature of the main component of the precursor, cellulose, was determined by thermogravimetric characterization of the dried precursor under nitrogen atmosphere. Figure 1 As shown, Figure 1 This is the thermogravimetric curve of Sargassum fusiformis in air atmosphere at a heating rate of 5℃ / min. Through analysis of the thermogravimetric curve, it is found that the main components begin to lose weight at 200℃, and no obvious weight loss occurs after 540℃. Starting at 200℃, the initial decomposition comes from the decomposition of protein and soluble polysaccharides, and the decomposition of lignin occurs at 240℃. After 380℃, the components undergo condensation and carbonization.

[0028] (3) The seaweed that has been processed into small segments is evenly dispersed in a quartz reaction boat. As a convertible implementation method, the material of the reaction boat can also be nickel, ceramic, or corundum, as long as it is resistant to high temperatures, does not react with the sample, and matches the size of the furnace body; the reaction boat is placed in a tubular furnace, and then the tubular furnace is purged with nitrogen at a nitrogen flow rate of 3-10 ml / min for 1-10 h. In this embodiment, the nitrogen flow rate is preferably 3 ml / min, and the purging time is preferably 2 h; thereby, the entire heating environment can be replaced with a nitrogen environment to avoid the presence of oxygen or other gases that may cause oxidation and other reactions during the carbonization process. Then, under a nitrogen flow, the temperature is raised from room temperature to the carbonization temperature at a heating rate of 5 °C / min. Under the protection of a nitrogen flow, the material is kept at an activation temperature of 900 °C for 120 min; (4) The porous carbon material obtained in step (3) is cooled to room temperature under a nitrogen flow to remove a small amount of metal impurities in the raw material, washed with water until neutral, dried and then carbonized for 60 minutes.

[0029] Through the above method, a porous carbon material is prepared.

[0030] The 4000 cm -1 Up to 400 cm -1 Infrared spectrum see Figure 2 A, 4000 cm of the prepared porous carbon material -1 Up to 400 cm -1 Infrared spectrum see Figure 2 B. As Figure 2 As shown in Figures 2A and 2B, the porous carbon material prepared by the method of this embodiment has obvious disappearance of CH stretching vibration peak, OH stretching vibration, COC vibration and aromatic core, which proves that the carbonization process is very thorough.

[0031] Figure 3 The figure is a low-pressure nitrogen gas adsorption-desorption isotherm of the porous carbon material powder obtained by the method of this embodiment. The nitrogen gas adsorption-desorption isotherm of the material is obtained by testing the Micromeritics TriStar Ⅱ 3020 adsorption instrument at 77K and 0-1atm. The solid points in the figure are adsorption curve points, and the empty points are desorption curve points. According to the adsorption-desorption curve, a sample with a larger BET specific surface area can be obtained in the 900°C sample. Through the nitrogen adsorption-desorption isotherm, the BET specific surface area of ​​the porous carbon-silicon composite material reaches 1200 square meters / gram.

[0032] Figure 4 The pore size distribution diagram of the porous carbon material obtained by the method of this embodiment calculated according to the DFT method is as follows: Figure 4As shown, the pore size distribution of porous carbon materials is around 1.0 nm.

[0033] Figure 5 This is the X-ray powder diffraction spectrum of the sample powder after the precursor was pyrolyzed at 900°C. The test was carried out by Shimadzu XRD-6000 X-ray diffractometer, copper target, test conditions of 40.0 kV, 30.0 mA, scanning speed 2.0 ° / min (2θ). Quartz plate was used as the sample carrier.

[0034] Figure 6 This is the high-pressure methane gas storage curve of the porous carbon-silicon composite material sample of this embodiment. The high-pressure gas storage data of this material was obtained by testing at room temperature, 1-35 Bar using the Shanghai University HPSA-2 PCT device. According to the curve, the adsorption capacity of the porous carbon material for methane at 35 Bar is 474V / V.

[0035] Figure 7 This is the thermogravimetric curve of the porous carbon-silicon composite material of the sample of this embodiment. The sample loses 3% weight before 400°C and no longer loses weight after 630°C. The ash mass is 7%, and the ash is mainly composed of Si element. The sample has good thermal stability, and the adsorption characteristics come from the joint contribution of C and Si.

[0036] Figure 8 This is the EDX test result of the sample in this embodiment.

[0037] Fig. 9 SEM test results of porous carbon materials. Example 2

[0038] The method of this embodiment is basically the same as that of embodiment 1, except that in step (3), the temperature of the tube furnace is controlled at 1000 degrees Celsius.

[0039] The nitrogen gas adsorption-desorption isotherm of the material was obtained by testing with a Micromeritics TriStar II 3020 adsorption instrument at 77K and 0-1atm. The solid points in the figure are adsorption curve points, and the empty points are desorption curve points. Through the nitrogen adsorption-desorption isotherm, the BET specific surface area of ​​the sample reached 824 square meters / gram. Example 3

[0040] The method of this embodiment is basically the same as that of embodiment 1, except that in step (3), the temperature of the tube furnace is controlled at 800 degrees Celsius.

[0041] The nitrogen gas adsorption-desorption isotherm of the material was obtained by testing with a Micromeritics TriStar II 3020 adsorption instrument at 77K and 0-1atm. The solid points in the figure are adsorption curve points, and the empty points are desorption curve points. Through the nitrogen adsorption-desorption isotherm, the BET specific surface area of ​​the sample reached 653 square meters / gram. Example 4

[0042] The method of this embodiment is basically the same as that of embodiment 1, except that the heating rate of the programmed temperature in step (3) is 2 degrees Celsius per minute, and the temperature is controlled at 800 degrees Celsius by a tubular furnace in step (3). Example 5

[0043] The method of this embodiment is basically the same as that of embodiment 1, except that the heating rate of the programmed heating in step (3) is 2 degrees Celsius per minute, and the temperature is controlled at 650 degrees Celsius by a tubular furnace in step (3). Example 6

[0044] The method of this embodiment is basically the same as that of embodiment 1, except that the heating rate of the programmed temperature in step (3) is 2 degrees Celsius / minute, the carbonization time is 60 minutes, and the inert gas used is argon.

[0045] Comparative Example

[0046] According to the theory proposed by Kimberly in 1992, since the size of methane is 0.414nm, the pore size of the activated carbon material is distributed between 0.8-1.2nm, which is equivalent to 2-3 molecular sizes. The methane molecules can be well fixed in the pores, which is suitable for storing methane gas. This explains the methane storage capacity of the pyrolysis-activated Sargassum samples and the methane storage capacity of activated rice husks. Given that the methane adsorption capacity of the carbonized Sargassum samples is higher than that of the activated rice husk-based activated carbon, and the activation process increases the process steps, preparation costs and post-processing costs and will cause equipment corrosion, economic losses and increase safety hazards, the process of direct carbonization of Sargassum is a more optimized process for preparing methane adsorbents, which has more practical application value in production.

[0047] The above are all preferred embodiments of the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, various equivalent modifications to the present invention belong to the protection scope of the claims attached to this application.

Claims

1. A method for preparing composite pellets using seaweed, characterized in that: The method is as follows: Step 1: Wash, dry and cut the seaweed into small pieces, and evenly spread them in a reaction container; Step 2: Place the reaction vessel in a furnace and purge the furnace with inert gas at a flow rate of 3-10 ml / min for 1-10 h; Step 3: Under the protection of inert gas, slowly increase the furnace temperature from room temperature to the activation temperature of 650-1000°C at a rate of 2-5°C / min. After activating for 60-120 minutes, a porous silicon-carbon material is obtained; Step 4: Cool the porous silicon-carbon material obtained in step 3 to room temperature. The cooling process is carried out under the protection of inert gas. After acid washing to remove impurities and water washing to neutrality, it is dried, heated at the same temperature for 60 minutes, and cooled to room temperature. Step 5: The porous carbon obtained in step 4 is mixed with clay, pressed into pellets, and sintered at 600-1000°C to obtain rigid porous carbon / silicate composite pellets suitable for filling into ANG tanks.

2. The method for preparing composite pellets using seaweed according to claim 1, characterized in that: The reaction container is made of quartz, nickel, ceramic or corundum.

3. The method for preparing composite pellets using seaweed according to claim 1, characterized in that: The inert gas is nitrogen or argon, the inert gas flow rate is 3 ml / min, and the purge time is 2 h.

4. The method for preparing composite pellets using seaweed according to claim 1, characterized in that: The furnace is a tubular furnace.

5. The method for preparing composite pellets using seaweed according to claim 1, characterized in that: After ball milling in step 4, the product is washed with 10%-36.5% hydrochloric acid to remove impurities and washed with water until neutral and then dried.

6. The method for preparing composite pellets using seaweed according to claim 1, characterized in that: The clay is high-silica clay, which is specifically montmorillonite, bentonite, kaolin or one or more combinations thereof. The granulation pressure is 10-40 MPa, and the sintering temperature is 650-1000°C.